2023
DOI: 10.1364/ao.487329
|View full text |Cite
|
Sign up to set email alerts
|

Loading test on the oil tank ground settlement performance monitored by an optical parallel scheme

Abstract: A loading test of the ground settlement (GS) performance of the oil tank must be examined before beginning its commercial service. This test requires the sensors to be installed around the oil tank, and the GS is measured while water is being filled in, where the liquid level is read with an ultrasonic radar equipment, etc., to indicate the applied water loads. During the service of the oil tank, loading and unloading corresponding to the oil inlet and outlet are the critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…When the electrical motor moves and satisfies the equal optical path difference condition as , a peak signal can be found in the interference pattern. Using this, the liquid level change can be continuously recorded, and the GS can be deduced [ 3 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…When the electrical motor moves and satisfies the equal optical path difference condition as , a peak signal can be found in the interference pattern. Using this, the liquid level change can be continuously recorded, and the GS can be deduced [ 3 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…From Figure 1 b, the readout at midnight shows the change is limited to within 3 mm for 1 week. Besides this, actual tests have demonstrated that in a loading process, the GS between the totally empty condition and totally full condition can reach about 7 mm [ 3 ]. Based on that, it is believed that in a short time (daytime < 12 h), the fluctuation of GS measurement should all entirely attributable to temperature uncertainty.…”
Section: Practical Test and Data Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to overcome these limitations, researchers have utilized the hydrostatic leveling system (HLS) technique. But, in the oil tank application, two main challenges need to be addressed for the HLS: ensuring fireproof safety and avoiding temperature interference [12].…”
Section: Introductionmentioning
confidence: 99%